The ethics of biotechnology - Sims, Tracey D; Gold, Gayle Friedman; Orhnberger, Jeanne; Forgey, Bob; Hill, Elliott; Athey, Brian; Baker, James; Fleck, Len; Kleff, Susanne; Morris, Jonathan,|cPhD; Films for the Humanities (Firm); Radish Creative Group (Hamilton, NJ : Films for the Humanities & Sciences, 2009)
A group of experts discuss the ethical and moral implications of biotechnology in the twenty-first century
"Based on books by Chelsea House Publishers, an imprint of Infobase Publishing, The ethics of biotechnology, by Jonathan Morris" -- Closing credits
"39779-K" -- Front cover
Editor, Curt Massof ; graphics, Chris Nierhaus, Curt Massof ; music, Yessian Music, Tracey D. Sims
Narrator, Gayle Friedman Gold ; commentary by Jeanne Orhnberger (Genetics Squared); Bob Forgey (ProNAi Therapeutics); Elliott Hill, Brian Athey, and James Baker (University of Michigan); Len Fleck (Michigan State University); and Susanne Kleff (MBI International)
DVD
Closed-captioned
Keywords: Biotechnology -- Moral and ethical aspects; Genetic engineering -- Moral and ethical aspects; Short films; Documentary films; Science films; Nonfiction films; Video recordings for the hearing impaired